2011
DOI: 10.1016/j.jclinepi.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A combined comorbidity score predicted mortality in elderly patients better than existing scores

Abstract: OBJECTIVE-To develop and validate a single numeric comorbidity score for predicting shortand long-term mortality, by combining conditions in the Charlson and Elixhauser measures.STUDY DESIGN AND SETTING-In a cohort of 120,679 Pennsylvania Medicare enrollees with drug coverage through a pharmacy assistance program, we developed a single numeric comorbidity score for predicting 1-year mortality, by combining the conditions in the Charlson and Elixhauser measures. We externally validated the combined score in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
742
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 843 publications
(784 citation statements)
references
References 28 publications
4
742
3
5
Order By: Relevance
“…A modified hypertension, abnormal renal and liver functions, stroke, bleeding, labile international normalized ratio, elderly, drugs, or alcohol score was used to represent bleeding risk15 (international normalized ratio history was not reflected in our score because laboratory values were not available). We applied a previously validated comorbidity score, as defined by Gagne and colleagues, to quantify comorbidity burden 16. Furthermore, we extracted data pertaining to health care use (number of inpatient hospital days, skilled nursing facility stay, and extended care stay) and medication use (insulin, statins, β blockers, calcium channel blockers, aspirin, clopidogrel, proton pump inhibitors, and nonsteroidal anti‐inflammatory drug use).…”
Section: Methodsmentioning
confidence: 99%
“…A modified hypertension, abnormal renal and liver functions, stroke, bleeding, labile international normalized ratio, elderly, drugs, or alcohol score was used to represent bleeding risk15 (international normalized ratio history was not reflected in our score because laboratory values were not available). We applied a previously validated comorbidity score, as defined by Gagne and colleagues, to quantify comorbidity burden 16. Furthermore, we extracted data pertaining to health care use (number of inpatient hospital days, skilled nursing facility stay, and extended care stay) and medication use (insulin, statins, β blockers, calcium channel blockers, aspirin, clopidogrel, proton pump inhibitors, and nonsteroidal anti‐inflammatory drug use).…”
Section: Methodsmentioning
confidence: 99%
“…3.1), we recorded the presence of comorbid conditions. 8 We also created a numerical comorbidity summary score based on the work of Gagne et al 9 …”
Section: Demographics and Comorbiditiesmentioning
confidence: 99%
“…However, all available mortality prediction models have been developed using data from a single study, but all from the United States and Western Europe (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which greatly limits their validity for use even in other high-income countries, let alone in the developing countries. For instance, a model developed using data from the Health and Retirement Study (HRS) in the United States showed poor performance when it was applied to older adults in England (18).…”
mentioning
confidence: 99%